Paciente femenino de 18 años de edad con fractura de peroné y anemia ferropénica. - Vera Acosta, Lisbeth Mercedes (2021)
The realization of this clinical case is of an 18-year-old female patient, a student from the city of Pichincha in the province of Manabí who entered the IESS Quevedo General Hospital after suffering a traffic accident where she was traveling as a co-pilot, entering by the emergency area where a fibula fracture and iron deficiency anemia were determined as a consequence of excessive blood loss. Objective: To improve the nutritional status of a female patient with a fibula fracture and iron deficiency anemia. Methodology: The development of this clinical case had a descriptive approach, since anthropometric, biochemical, clinical and dietary data were collected. Results: With the evaluation of the nutritional status, it was determined that the patient had a normal nutritional status, but her biochemical tests and clinical evaluation determined that the patient had iron deficiency anemia. Conclusion: It was possible to improve the nutritional status of the patient with the inclusion of more iron intake in the diet, promoting in her the change to a healthy diet that includes all the macro and micronutrients that allow her to have an optimal state of health.